Frequent infection of wild boar with atypical porcine pestivirus (APPV). Issue 4 (12th March 2018) - Cagatay, G. N.; Antos, A.; Meyer, D.; Maistrelli, C.; Keuling, O.; Becher, P.; Postel, A.
Summary: The recently identified atypical porcine pestivirus (APPV) was demonstrated to be the causative agent of the neurological disorder "congenital tremor" in newborn piglets. Despite its relevance and wide distribution in domestic pigs, so far nothing is known about the situation in wild boar, representing an important wild animal reservoir for the related classical swine fever virus. In this study, 456 wild boar serum samples obtained from northern Germany were investigated for the presence of APPV genomes and virus‐specific antibodies. Results of real‐time RT‐PCR analyses revealed a genome detection rate of 19%. Subsequent genetic characterization of APPV ( n  = 12) from different hunting areas demonstrated close genetic relationship and, with exception of APPV from one location, displayed less than 3.3% differences in the analysed partial NS3 encoding region. Furthermore, indirect E rns ELISA revealed an antibody detection rate of approx. 52%, being in line with the high number of viremic wild boar. Analysis of fifteen wild boar samples from the Republic of Serbia by E rns antibody ELISA provided evidence that APPV is also abundant in wild boar populations outside Germany. High number of genome and seropositive animals suggest that wild boar may serve as an important virus reservoir for APPV.